Combined small cell and squamous cell carcinoma of the larynx - Kołodziej, Paweł; Ostasiewicz, Paweł; Ziółkowski, Piotr (Contemporary Oncology/Współczesna Onkologia, 2012)
A case of combined small cell and squamous cell carcinoma of the larynx in a male patient in the sixth decade of life is reported. The etiopathogenesis of this combined tumor remains unclear; however, a number of hypotheses were proposed in the past including the pivotal role of Kulchitsky, squamous cells and the glandular cells. The gene mutations may also play an important role in laryngeal carcinogenesis. This unusual type of laryngeal combined carcinoma has previously been reported worldwide in only 17 cases. This is an extremely rare tumor the histological nature of which makes the diagnosis more complicated than in other types of laryngeal cancers. The diagnosis of this carcinoma is based on light microscopy and should be supported by immunohistochemical studies. In our case, the tumor was growing in the left pyriform sinus. Metastatic neck lymph nodes were found on the left side, but no distant metastases were observed. Microscopic sections revealed a combined tumor composed of small cell carcinoma neuroendocrine type and non-keratinizing squamous cell carcinoma. Positive reaction to p16, bcl-2, thyroid transcription factor 1, synaptophysin and chromogranin A in the small cell neuroendocrine type carcinoma component was observed. The cells from squamous cell carcinoma component showed positive reaction to p63, high-molecular-weight cytokeratin and cytokeratin 5/6.